Edible insects: Challenges and prospects. Issue 4 (19th April 2022) - van Huis, Arnold
Abstract: An overview is given on recent developments in insects as food and food by reviewing the literature which has appeared during the last few years on edible insects. An outlook to the future is provided. About a decade ago, the attention shifted from harvesting insects in the tropics to farming insects all over the world for food and feed applications. Most production is targeted towards pet food, but it will turn to aquafeed in the next two decades. More than 80% of all publications dealing with edible insects appeared during the last five years. Crickets and mealworms are used for human food while the black soldier fly is the main species used as animal feed. The criteria to choose insect species are automation, cheap substrates, disease avoidance, and market potential. Genetics are increasingly explored to improve production. The environmental impact of producing insects compares well to other alternative proteins, in particular their capacity to degrade organic waste streams. Edible insects are not only a good source of nutrients but also seem to provide health benefits not only for humans and animals, but also for plants (left over substrate). The challenge of convincing Western consumers is reviewed and whether sustainability is an issue. Processing techniques are being developed. The sector of insects as food and feed is developing fast thanks to an increasingly conducive legislative framework. It will progress further, provided that the insect industry, academia, governmental organizations, and public society closely cooperate.